Prefrontal cortex cell proliferation of adult rats after chronic stress treated with ethanolic extract of Centella asiatica (L) Urban. - Yuniasih Mulyani Jubeliene Taihuttu; Ginus Partadiredja; Dwi Cahyani Ratna Sari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
The decrease of proliferation level of cells in several regions of adult brain is found afterstress exposure. One of such area is prefrontal cortex. Herbal medicine as antistresshas been used widely. Centella asiatica (L) Urban extract was reported to have potentcompounds to increase brain function. The objective of this study is to investigate theeffects of ethanolic extract C. asiatica on cell proliferation of the adult prefrontal cortexin rats (PFC) after chronic stress. Adult male Sprague-Dawley rats, weighing 260-390g were randomly assigned into six experimental groups, with five rats per group, i.e.Group 1 as nomal control without chronic stress, Group 2 as stress control, Group 3 aspositive control given fluoxetine, Group 4-6 as treatment groups given 150; 300 and 600of ethanolic extrac C. asiatica, respectively. Extract were administered orally to the ratsfollowing a period of restraint duration of 6 hours/day for 21 days. Bromodeoxyuridine(BrdU) immunohistochemistry was used to label the proliferated cells. Physical fractionatormethod was used to estimate the total number of proliferated cells. One-way analysis ofvariance (ANOVA) followed by Tukey post hoc test was used to evaluate the differencebetween groups. BrdU-labeled cells on medial prefrontal cortex were as follows:1715.3±1345.1 (Group 1), 2659.2±2250.6 (Group 2), 4077.4±2415.3 (Group 3),1784.1±908.3 (Group 4), 3056.6±4263.3 (Group 5), and 2153.4±2259.4 (Group 6).No significance difference between groups was observed (p>0.05). In conclusion, theadministration of ethanolic extract of C. asiatica does not influence cell proliferation onprefrontal cortex of rats after chronic stress.